SIMULAÇÃO DO CLIMA URBANO COMO FERRAMENTA PARA O DESENVOLVIMENTO SUSTENTÁVEL - Morsch, Maiara; Petry, Bruna; Peruzzo, Kalindy Granella; Tomasi, Sabrina; Tavares, Rafael; Marques, Juliane Avila (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The urban climate differs from the climate of the city in question, since it changes by the specific characteristics of the urban enclosure. In this way cities are formed by a variety of microclimates that are often drastically altered causing damage to the environmental and to people. The study is important in order to look for alternatives to reduce these negative effects in search of environmentally healthy cities. In this sense, several simulation tools emerge to aid in research, such as the ENVI-met software that has been widely disseminated. The objective of this research is to evaluate the acuity of this tool in order to be used in the methodology of a doctoral thesis in progress. The methodology was based on the study of the microclimate in a real case as a feasibility test. In this situation was carried out a physical survey of the site, a climatic survey with dataloggers and finally the simulation. The results generated indicated the positive use of the tool.